Firstborn child readiness for a new sibling: a case study of birth-order challenges and coping for parents - Zakaria, Faizah; Abd Hamid, Siti Rafiah (Institut Sosial Malaysia, 2020)
Transition to siblinghood can be very stressful for many families due to a newly born sibling's arrival. The study's primary purpose is to explore the mother's preparation experiences with regard to the firstborn child's behavior before and after in response to the birth of a second-born sibling. The current study is a phenomenological examination of the firstborn child's readiness for a new sibling using a sample of two mothers who are currently having two children. Eighteen categories that emerged from the raw data were further categorized into four general themes: support systems, talk to your child, positive post-birth behavior, and malicious post-birth behavior. The themes developed in this study illustrate mothers' perceptions of their firstborn child's behavior in response to a second-born sibling's birth. It is hoped that this study would enlighten on the critical period and changes in the firstborn child's adjustment and family relationships following the sibling's birth.